2020
DOI: 10.3390/ph13120439
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Interactions between Atypical Antipsychotics and Anti-Infective Agents

Abstract: This is a comprehensive review of the literature on drug interactions (DIs) between atypical antipsychotics and anti-infective agents that focuses on those DIs with the potential to be clinically relevant and classifies them as pharmacokinetic (PK) or pharmacodynamic (PD) DIs. PubMed searches were conducted for each of the atypical antipsychotics and most commonly used anti-infective agents (13 atypical antipsychotics by 61 anti-infective agents/classes leading to 793 individual searches). Additional relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 126 publications
(180 reference statements)
0
19
0
2
Order By: Relevance
“…The pharmacokinetic variables that may influence clozapine metabolism including DDIs, obesity, inflammation, geriatric age, and pregnancy have been reviewed in Supplementary Box S3 1 21 29 40 56 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 .…”
Section: Advances In Clozapine Pharmacokinetics Not Included In the Us Package Insertmentioning
confidence: 99%
“…The pharmacokinetic variables that may influence clozapine metabolism including DDIs, obesity, inflammation, geriatric age, and pregnancy have been reviewed in Supplementary Box S3 1 21 29 40 56 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 .…”
Section: Advances In Clozapine Pharmacokinetics Not Included In the Us Package Insertmentioning
confidence: 99%
“…As the number of medications taken by the individual patient increases, so does the potential for drug-drug interactions that have clinically important consequences [ 1 ]. Recent regulatory actions by the US Food and Drug Administration (FDA) remind us of the potential risk of important drug interactions with anti-infective agents [ 2 ]. In the early 1990s, patients experienced serious cardiac toxicity after taking antihistaminic drugs in combination with macrolide antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…57 Attention should be paid to the concomitant administration of strong cytochrome P450 3A4 inhibitors or inducers, 58 as reported in the related SmPC, 59 and in a recent review that showed the effect of concomitant administration of some anti-infective agents on lurasidone metabolism, underlining the supposed similarity with quetiapine and cariprazine. 60 Lastly, akathisia is a possible side effect described for the drug, reported in some cases either by naïve patients or following the switch from another treatment. This condition can be solved by the adoption of concomitant treatment with benzodiazepines or β-blockers.…”
Section: Discussionmentioning
confidence: 99%